Blaming consumers: Ideology and European austerity. (November 2019) - Bradshaw, Alan; Ostberg, Jacob
This study analyzes a particular ideology of austerity as it spreads across Europe and reappears across diverse discourses. This ideology mobilizes the figure of the feckless consumer, who has overspent, who must come to regard their consumption as stupid, and therefore will accept austerity; not just as an inevitable outcome of bad decisions, but as holding the potential for moral redemption. We argue that ideology correlates this micro-frame of the feckless consumer with the macro condemnation of government expenditure and therefore is a hinge upon which the dissemination of austerity turns. The argument is developed by contrasting a Swedish television programme called Luxury Trap with the so-called 'bail-out' of the Irish state, as well as broader experiences of a pan-European discourse. Just as Luxury Trap's hapless debtors are obliged to recognize their own stupidity through a process of brutal mortification, we argue that the Irish population has been mortified by an elite-driven narrative that measures consumption and expenditure as a gross average that reveals universal guilt and consumer excess. We see this powerful narrative implicating entire nations, obfuscating critical political economic analysis, and setting the ideological scene through which deep austerity programmes, ruinous to households and social infrastructures and starkly punitive to individuals, are pushed through. Critical to our argument is the over-determined status of the commodity itself whose invocation is central to the interpellation of a populace as excessive consumers. Instead of analysing social relations and neoliberalism's contradictions, resentment and critique focusses upon material things, as though, for example, a plasma television was in itself a dangerous problem.